Parents in the pigpen, pigs in the tub - Ehrlich, Amy, 1942- (Dial Books for Young Readers, 1993)
Tired of their usual routine, the farm animals insist on moving into the house, so the family decides to move into the barn, but eventually everyone tires of this new arrangement.